(untitled) (International Journal of Nursing Education, 2022)
Background: Children with severe acute malnutrition are therapeutically managed in the nutritional rehabilitation centres in terms of diet and required medicines based on their medical complication. There is visible improvement in the treatment outcome indicators at a minimal stay of fifteen days in nutritional rehabilitation centre. Objectives: Study objective was to assess the associated actors of SAM and to identify the treatment outcome among under five children admitted in nutritional rehabilitation centres. Methods: Quantitative approach with descriptive research design was adopted. A total of 62 samples were taken by using non-probability convenience sampling. Data were collected by using interviewer administered questionnaire on demographic characteristics and associated factors of SAM. Health assessment was done by the structured outcome indicators on admission, at one week of treatment and on discharge to identify the treatment outcome. Result: Findings of the study revealed that there were significant association between occupation of mother and exclusive breastfeeding practice at 0.05 level of significance as the p value is < 0.05*. The repeated measure ANOVA analysis shows that there are significant changes occurring in the treatment outcome indicators from admission to discharge as the p value is 0.00* and the selected treatment outcome weight is associated with age of the child at 0.05 level of significance. Conclusion: Hence the treatment outcome of SAM is good in terms of outcome indicators. Lack of exclusive breastfeeding practices due to occupation of mother is the factor associated with SAM.